Extremely Active Organocatalysts Enable a Highly Enantioselective Addition of Allyltrimethylsilane to Aldehydes. (6th October 2016) - Kaib, Philip S. J.; Schreyer, Lucas; Lee, Sunggi; Properzi, Roberta; List, Benjamin
Abstract: The enantioselective allylation of aldehydes to form homoallylic alcohols is one of the most frequently used carbon–carbon bond‐forming reaction in chemical synthesis and, for several decades, has been a testing ground for new asymmetric methodology. However, a general and highly enantioselective catalytic addition of the inexpensive, nontoxic, air‐ and moisture‐stable allyltrimethylsilane to aldehydes, the Hosomi–Sakurai1 reaction, has remained elusive.2 3 Reported herein is the design and synthesis of a highly acidic imidodiphosphorimidate motif (IDPi), which enables this transformation, thus converting various aldehydes with aromatic and aliphatic groups at catalyst loadings ranging from 0.05 to 2.0 mol % with excellent enantioselectivities. Our rationally constructed catalysts feature a highly tunable active site, and selectively process small substrates, thus promising utility in various other challenging chemical reactions.